Sport supporting act: terminology issues - Petr Vlček (Palacký University Olomouc, 2013)
BACKGROUND: The text deals with terminology issues from an interdisciplinary point of view. It is based on two diﬀerent disciplines, law and kinanthropology, in an area of their overlap. AIM: The aim of the author is to point out some possible legislative problems, which could arise due to the current reading of the sport supporting act (Act no. 115/2001). The second aim of the author is to contribute to the discussion of kinantropologists (possibly also the educational researchers and lawyers) and to stress the importance of the systematic approach to terminology formulation. METHODS: The author uses the method of language interpretation. We also use the basic analytical methods, induction and deduction, while we stress the systematic approach to the term formulation. RESULTS: The analysis of the sport supporting act terminology shows some specific legislative problems, which could arise due to the definition of sport in the sport supporting act. The author discusses a possible alternative solution. CONCLUSION: According to the opinion of the author, clear, obvious and unified terminology of kinantropologists as specialists in their discipline should represent a source, from which other sciences could derive their terminology. Defined and inexpert terminology used in other disciplines should not be used as an argument for its adopting in kinanthropology.